Association between Primary Caregiver Education and Cognitive and Language Development of Preterm Neonates - Asztalos, Elizabeth V.; Church, Paige T.; Riley, Patricia; Fajardo, Carlos; Shah, Prakesh S.; for the Canadian Neonatal Network and Canadian Neonatal Follow-up Network Investigators (American Journal of Perinatology, 2017)
Objective This study aims to explore the association between primary caregiver education and cognitive and language composite scores of the Bayley Scales of Infant and Toddler Development, 3rd ed. (Bayley-III) in preterm infants at 18 to 21 months corrected age.Design An observational study was performed on preterm infants born before 29 weeks' gestation between 2010 and 2011. Primary caregivers were categorized by their highest education level and cognitive and language composite scores of the Bayley-III were compared among infants between these groups with adjustment for perinatal and neonatal factors.Results In total, 1,525 infants/caregivers were included in the multivariate analysis. Compared with those with less than a high school education, infants with primary caregivers who received partial college/specialized training displayed higher cognitive (adjusted difference [AD]: 4.6, 95% confidence interval [CI]: 1.8–7.4) and language scores (AD: 4.0, 95% CI: 0.8–7.1); infants with primary caregivers with university graduate education or above also demonstrated higher cognitive (AD: 6.4, 95% CI: 2.6–10.1) and language scores (AD: 9.9, 95% CI: 5.7–14.1).Conclusion Higher levels of education of the primary caregiver were associated with increased cognitive and language composite scores at 18 to 21 months corrected age in preterm infants.
Keywords: neurodevelopmental outcomes; very preterm infants; primary caregiver education; cognitive development; language development